Cause-related marketing: An experimental study about how the product type and the perceived fit may influence the consumer response - Iguácel Melero; Teresa Montaner (European Journal of Management and Business Economics (EJM&BE), 2016)
Although previous cause-related marketing literature has examined the role of the nature of the product and the perceived fit between the product and the cause, there is no clear consensus yet regarding the effect of these variables. This study contributes to existing literature by shedding light on the role that these two key factors have on consumer response. A 2 (utilitarian products vs. hedonic products)2 (perceived fit: high vs. low) between-subjects factorial design was used to test the hypotheses. The results indicate that the nature of the promoted product used in the cause-related marketing campaign influences both brand attitude and purchase intention. Specifically, the attitude towards the brand was greater for the hedonic products than the utilitarian ones. By contrast, cause-related marketing campaigns linked to utilitarian products lead to higher purchase intentions. In addition, perceived fit between the product and the cause seems to play a key role, as this variable positively influences both the credibility of the campaign and the attitude towards the brand. The results provide useful guidelines for marketers in designing their cause-related marketing initiatives.
Keywords: M31; 650; Cause-related marketing; Consumer response; Perceived fit; Product type